Beyond Active-Passive: Towards the Next Stage of Social Media and Mental Health Research - Meier, Adrian; Ellison, Nicole; Reinecke, Leonard; Valkenburg, Patti M. (2026)
How social media impact users’ mental health and well-being is a critical question discussed fiercely by publics around the globe and researchers across disciplines. To overcome challenges of earlier “screen time” research, many recent studies adopted the active-passive approach. This model dichotomizes social media use into “active” social exchanges and “passive” consumption, with active use yielding social benefits and passive use resulting in harmful upward comparison and envy. Yet, this model has produced surprisingly inconsistent evidence, sparking recent theoretical debates and extensions. Here, we critically synthesize six remaining challenges for the active-passive approach and develop an agenda that outlines why and how the field needs to go beyond active-passive. Specifically, we envision three routes for future research alongside an integrated communication-centered model, which proposes to focus research efforts on message effects, cross-platform experiences, and technology features and affordance
https://cris.fau.de/converis/publicweb/Publication/335324418
Keywords: social media; active-passive use; mental health; well-being; media-affects